Direct and indirect cardiovascular and cardiometabolic sequelae of the combined anti-retroviral therapy on people living with HIV - Batta, Yashvardhan; King, Cody; Cooper, Farion; Johnson, John; Haddad, Natasha; Boueri, Myriam G.; DeBerry, Ella; Haddad, Georges E. (Frontiers in Physiology, 2023)
With reports of its emergence as far back as the early 1900s, human immunodeficiency virus (HIV) has become one of the deadliest and most difficult viruses to treat in the era of modern medicine. Although not always effective, HIV treatment has evolved and improved substantially over the past few decades. Despite the major advancements in the efficacy of HIV therapy, there are mounting concerns about the physiological, cardiovascular, and neurological sequelae of current treatments. The objective of this review is to (1) highlight the different forms of antiretroviral therapy, how they work, and any effects that they may have on the cardiovascular health of patients living with HIV, and to (2) explore the new, more common therapeutic combinations currently available and their effects on cardiovascular and neurological health. We executed a computer-based literature search using databases such as PubMed to look for relevant, original articles that were published after 1998 to current year. Articles that had relevance, in any capacity, to the field of HIV therapy and its intersection with cardiovascular and neurological health were included. Amongst currently used classes of HIV therapies, protease inhibitors (PIs) and combination antiretroviral therapy (cART) were found to have an overall negative effect on the cardiovascular system related to increased cardiac apoptosis, reduced repair mechanisms, block hyperplasia/hypertrophy, decreased ATP production in the heart tissue, increased total cholesterol, low-density lipoproteins, triglycerides, and gross endothelial dysfunction. The review of Integrase Strand Transfer Inhibitors (INSTI), Nucleoside Reverse Transcriptase Inhibitors (NRTI), and Non-Nucleoside Reverse Transcriptase Inhibitors (NNRTI) revealed mixed results, in which both positive and negative effects on cardiovascular health were observed. In parallel, studies suggest that autonomic dysfunction caused by these drugs is a frequent and significant occurrence that needs to be closely monitored in all HIV+ patients. While still a relatively nascent field, more research on the cardiovascular and neurological implications of HIV therapy is crucial to accurately evaluate patient risk.